( 2 4 + 4 1 ) ( 4 4 + 4 1 ) ⋯ ( ( 2 n ) 4 + 4 1 ) ( 1 4 + 4 1 ) ( 3 4 + 4 1 ) ⋯ ( ( 2 n − 1 ) 4 + 4 1 )
Given that the expression above can be simplified to ( a n 2 + b n + c ) − 1 for constants a , b , c , find 2 1 ( a − b + c ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hi, that's an elegant solution! :-) Didn't consider that approach yesterday. Thumbs up to you.
Actually, your solution was a short step away. Assuming that the answer must have the form of a n 2 + b n + c 1 , you showed that it must be 8 n 2 + 4 n + 1 1 .
If so, this implies that ( 2 n ) 4 + 4 1 ( 2 n − 1 ) 4 + 4 1 = 8 n 2 + 4 n + 1 8 ( n − 1 ) 2 + 4 ( n − 1 ) + 1 . This helps us to motivate the telescoping product, instead of it being something that is mysteriously obtained.
Of course, if we do not know the form of the answer, then we must have some speculative guesses about what it is like. A priori, there is no reason why it must be so nice (other than the fact that it is set as a question).
Let
f
(
n
)
=
∏
i
=
1
n
(
(
2
i
)
4
+
4
1
)
∏
i
=
1
n
(
(
2
i
−
1
)
4
+
4
1
)
The exercise states that f ( n ) = a n 2 + b n + c 1 , so we can solve the problem by computing f ( 1 ) , f ( 2 ) and f ( 3 ) , and solve the emerging system of linear equations. Since f ( 1 ) = 1 3 1 , f ( 2 ) = 4 1 1 and f ( 3 ) = 8 5 1 , we get
f ( 1 ) 1 f ( 2 ) 1 f ( 3 ) 1 = a + b + c = 1 3 = 4 a + 2 b + c = 4 1 = 9 a + 3 b + c = 8 5
The solution for this system of linear equations is a = 8 , b = 4 and c = 1 . Hence, 2 1 ( a − b + c ) = 2 1 ⋅ 5 = 1 0 5
Now that you "know" we must have a = 8 , b = 4 , c = 1 , can you prove it for all n ?
Hint: Telescoping Product.
For proving , it would be easier to take the help of PMI , is there any other way?
Problem Loading...
Note Loading...
Set Loading...
Just to improve Sir Martin Sergio's Solution :)
Let
f ( n ) = ∏ i = 1 n ( ( 2 i ) 4 + 4 1 ) ∏ i = 1 n ( ( 2 i − 1 ) 4 + 4 1 )
Completing the squares,
f ( n ) = ∏ i = 1 n ( ( ( 2 i ) 2 + 2 1 ) 2 − ( 2 i ) 2 ) ∏ i = 1 n ( ( ( 2 i − 1 ) 2 + 2 1 ) 2 − ( 2 i − 1 ) 2 )
But this is clearly difference of two squares,
f ( n ) = ∏ i = 1 n [ ( ( ( 2 i ) 2 + 2 1 ) − ( 2 i ) ) ( ( ( 2 i ) 2 + 2 1 ) + ( 2 i ) ) ] ∏ i = 1 n [ ( ( ( 2 i − 1 ) 2 + 2 1 ) − ( 2 i − 1 ) ) ( ( ( 2 i − 1 ) 2 + 2 1 ) + ( 2 i − 1 ) ) ]
The portion
( 2 i − 1 ) 2 + 2 1 + ( 2 i − 1 ) = 4 i 2 − 4 i + 1 + 2 i − 1 + 2 1 = 4 i 2 − 2 i + 2 1
But the portion
( ( 2 i ) 2 + 2 1 ) − ( 2 i ) ) = 4 i 2 − 2 i + 2 1 = ( 2 i − 1 ) 2 + 2 1 + ( 2 i − 1 )
Therefore the two factors will cancel leading to,
f ( n ) = ∏ i = 1 n [ ( ( 2 i ) 2 + 2 1 ) + ( 2 i ) ] ∏ i = 1 n [ ( ( 2 i − 1 ) 2 + 2 1 ) − ( 2 i − 1 ) ) ]
Similarly, other factors will also cancel leading to
f ( n ) = ( ( 2 n ) ) 2 + 2 1 ) + ( 2 n ) ) ( ( 2 ( 1 ) − 1 ) 2 + 2 1 ) − ( 2 ( 1 ) − 1 )
f ( n ) = 4 n 2 + 2 1 + 2 n 2 1
f ( n ) = 8 n 2 + 4 n + 1 1
a = 8
b = 4
c = 1
2 1 ( a − b + c ) = 2 1 ( 8 − 4 + 1 ) = 2 1 ( 5 ) = 1 0 5